Prevalence of thrombophilia and thrombotic events in patients with fabry disease in a Reference Center for Lysosomal Disorders in Southern Brazil - Dick, Jéssica; Leistner-Segal, Sandra; Vairo, Filippo Pinto; Giugliani, Roberto; Schwartz, Ida Vanessa Doederlein (Clinical and Biomedical Research, 2016)
Introduction: Venous thromboembolism (VTE) is a multifactorial genetic disorder that occurs in approximately one in a thousand adults per year. Because there is no laboratory test or clinical marker useful for predicting which patients with Fabry disease may develop thrombotic events, this study aimed to determine whether there is a hereditary predisposition to hypercoagulation in these patients. Methods: The prevalence of p.R506Q mutation in the factor V gene and of c.G20210A mutation in Factor II (prothrombin) gene was evaluated in 39 patients with Fabry disease fromSouthern Brazil and correlated with clinical findings. The DNA analysis was performed by real-time polymerase chain reaction on genomic DNA using TaqMan probes. Results: In this group of patients, the frequency of mutation in the prothrombin gene was 1.28%, whereas no patient showed mutation in the factor V gene; additionally, there was no correlation between these mutations and the incidence of thrombotic events. Conclusion: Hereditary thrombophilia due to mutations in factor V and prothrombin genes does not seem to be related to thrombotic events in Fabry patients in our cohort, although studies in larger cohorts and the inclusion of additional factors may be required to determine if a correlation exists. Introdução: O tromboembolismo venoso (TEV) é uma desordem genética multifatorial que ocorre em aproximadamente um em cada mil adultos por ano. Pelo fato de não existir nenhum teste de laboratório ou marcador clínico útil para predizer quais pacientes com a doença de Fabry podem desenvolver eventos trombóticos, este estudo foi realizado com o objetivo de determinar se existe uma predisposição hereditária para hipercoagulação nesses pacientes. Métodos: A prevalência da mutação p.R506Q no gene do fator V e da mutação c.G20210A no gene do fator II (protrombina) foi avaliada em 39 pacientes com doença de Fabry do Sul do Brasil e associada com achados clínicos. A análise do DNA genômico foi realizada por reação em cadeia da polimerase (polymerase-chain reaction, PCR) em tempo real utilizando sondas TaqMan. Resultados: Neste grupo de pacientes, a frequência da mutação no gene da protrombina foi de 1,28%, enquanto que nenhum paciente apresentou a mutação no gene do fator V, não havendo correlação entre essas mutações e a incidência de eventos trombóticos. Conclusão: A trombofilia hereditária devido às mutações nos genes fator V e protrombina parece não estar relacionada a eventos trombóticos em pacientes com Fabry em nossa coorte, embora estudos em coortes maiores e a inclusão de fatores adicionais possam ser necessários para determinar se existe uma correlação.